1999
DOI: 10.1159/000016673
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic and Sensory Innervations Are Heterogeneously Distributed in Relation to the Blood Vessels at the Extensor carpi radialis brevis Muscle Origin of Man

Abstract: By using immunohistochemistry and antibodies to a general nerve marker, protein gene product (PGP) 9.5, the overall innervation at the extensor carpi radialis brevis (ECRB) muscle origin was investigated in patients with tennis elbow and in healthy controls. The autonomic innervation was studied by using antibodies to neuropeptide Y (NPY), tyrosine hydroxylase (TH), and vasoactive intestinal peptide (VIP). The sensory innervation was visualized by using antibodies to substance P and calcitonin gene-related pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
3
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 36 publications
3
38
3
2
Order By: Relevance
“…However, recent research has clarified the innervation at the ECRB muscle origin, and showed the presence of sensory nerve fibers (Ljung et al 1999a). Using immunohistochemistry and antibodies to the neuropeptides substance P (SP) and calcitonin gene-related peptide (CGRP), SP-and CGRP-like immunoreactivity at the muscle origin has been demonstrated (Ljung et al 1999b). It is known that SP and CGRP have afferent functions (transmitting nociceptive information to the spinal cord), but also efferent functions like involvement in vasodilatation and plasma extravasation (so-called neurogenic inflammation) (Wiesenfeld-Hallin and Xu 1993).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research has clarified the innervation at the ECRB muscle origin, and showed the presence of sensory nerve fibers (Ljung et al 1999a). Using immunohistochemistry and antibodies to the neuropeptides substance P (SP) and calcitonin gene-related peptide (CGRP), SP-and CGRP-like immunoreactivity at the muscle origin has been demonstrated (Ljung et al 1999b). It is known that SP and CGRP have afferent functions (transmitting nociceptive information to the spinal cord), but also efferent functions like involvement in vasodilatation and plasma extravasation (so-called neurogenic inflammation) (Wiesenfeld-Hallin and Xu 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind using sclerotherapy in tendinopathy is based on the finding that there is a proliferation of small blood vessels in areas of tendinopathy. Nerve fibers appear to travel in close proximity to these areas of neovascularization [24,95,97]. It is possible these nerve fibers are the pain generators in tendinopathy.…”
Section: Sclerotherapymentioning
confidence: 99%
“…As for tendons, we were recently able to demonstrate the presence of sensory and autonomic neuropeptides in normal Achilles tendon of the rat [1,2]. These neuropeptides have also been found in tissues from patients with lateral elbow tendinosis [24,25]. Calcitonin gene-related peptide (CGRP), representing the sensory nervous system, is known to act vasodilatory, to participate in the regulation of angiogenesis, proliferation of fibroblasts and synoviocytes [7,16,38] as well as synthesis of cytokines and growth factors [8,28].…”
Section: Introductionmentioning
confidence: 99%